2002
DOI: 10.1161/01.str.0000018589.56991.ba
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitors and the Risk of Stroke

Abstract: Background and Purpose-Selective serotonin reuptake inhibitors (SSRIs) have been associated with increased risk of bleeding complications, possibly as a result of inhibition of platelet aggregation. Little is known about the risk of intracerebral hemorrhage in users of SSRIs and whether the effect on platelet aggregation reduces the risk of ischemic stroke. We used population-based data to estimate the risk of hemorrhagic and ischemic stroke in users of SSRIs. Methods-We performed a nested case-control study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
2
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 19 publications
1
85
2
3
Order By: Relevance
“…[11][12][13] Other drugs that may be associated with a decreased or increased risk of stroke include antiplatelet drugs, anticoagulants, statins, thiazide diuretics, estrogen-containing drugs, selective serotonin reuptake inhibitors, and antipsychotics. 1,[14][15][16][17][18] Its use in THR patients in relation with perioperative stroke, however, remains unknown.The objectives of this study were to evaluate timing of stroke after THR compared with matched control subjects Background and Purpose-Stroke is a potentially fatal complication of total hip replacements (THR). However, timing of stroke in THR patients compared with matched controls and influence of drug use remain unknown.…”
mentioning
confidence: 99%
“…[11][12][13] Other drugs that may be associated with a decreased or increased risk of stroke include antiplatelet drugs, anticoagulants, statins, thiazide diuretics, estrogen-containing drugs, selective serotonin reuptake inhibitors, and antipsychotics. 1,[14][15][16][17][18] Its use in THR patients in relation with perioperative stroke, however, remains unknown.The objectives of this study were to evaluate timing of stroke after THR compared with matched control subjects Background and Purpose-Stroke is a potentially fatal complication of total hip replacements (THR). However, timing of stroke in THR patients compared with matched controls and influence of drug use remain unknown.…”
mentioning
confidence: 99%
“…Whether the current use of SSRIs has some protective effect or not is still unclear, and further research is in demand. The findings from the study by Bak et al 27 warrant further studies that should distinguish whether the increased risk for stroke is clearly attributed to previous use of SSRIs or simply because of premature withdrawal of SSRIs in the treatment of depression. In addition, the findings suggested that the current use of anticoagulation therapy or antihypertensive drugs was associated with an increased risk of hemorrhagic stroke.…”
mentioning
confidence: 85%
“…A recent English cohort study 26 suggested weak evidence to support the hypothesis or the link between SSRIs and the precipitation of bleeding events at a population level. The nested case-control study from Denmark reported in this issue of Stroke, 27 however, showed that current use of SSRIs was not associated with an increased the risk of hemorrhagic and ischemic stroke. Previous publications have suggested associations between the use of SSRIs and a decreased risk of acute myocardial infarction and stroke.…”
mentioning
confidence: 86%
“…Two studies by Sauer and colleagues suggested that SSRI antidepressants, but not non-SSRI anti-depressants, reduced the incidence of MI (150,151). In contrast Meier and colleagues saw no protective effects of SSRIs against a first MI (152), and Bak and colleagues reported that SSRIs did not decrease the risk of ischemic stroke or increase the risk of intracerebral hemorrhage (153). Consequently, it appears that the critical basic and clinical studies that would establish, or otherwise, the role of SSRIs as antithrombotics remain to be carried out.…”
Section: The Serotonin Handling Systemmentioning
confidence: 99%